EPIDEMIOLOGY, PROGNOSIS AND RISK FACTORS FOR DEVELOPMENT OF ONCOLOGICAL DISEASES AS EARLY DIAGNOSTIC OF DENTAL PROBLEMS IN THE CHILDREN (World Science, 2021)
Introduction. In the world trends in incidence and death rates for all cancers combined and for the leading cancer types by sex, racial/ethnic group, and age were estimated by analysis and characterized by the average annual percent change during recent 5 years. Aim of research: to determine epidemiology of oncological diseases in the children population of rural clusters due to the chemical contamination of drinking water sources. Materials and methods. Analysis of water-related health indicators in the children population.  Drinking water quality monitoring included studies of chemical and salt composition of water from centralized (38260 studies) and decentralized (24586 studies) water supply systems carried out in rural clusters of Dnipropetrovsk region. Results. As a result of discriminant analysis, a plausible model probable development of cancer among children population in rural clusters of Dnipropetrovsk region, which consumed drinking water from decentralized drinking water sources was obtained. Conclusions. According to the correlation analysis was determined that oncological morbidity among children population responded quickly to the changes in salt and chemical composition of water from centralized and decentralized drinking water systems. In 3, 4, 5, 6 clusters of Dnipropetrovsk region high levels of morbidity this class of diseases (r=0,763, p=0,077) were observed in children who consume wells water with high nitrate content (at the limit of MPC 45 mg / dm3).  It was established that prognostic capacity for a model of development cancer in children under 14 years is 34%. During 2014–2019 years tendency of negative growth of tumors in the children population of Dnipropetrovsk region in all clusters was established: 1 (-20.9 %), 2  (-37.5 %), 3 (-31.1 %), 4 (-33.8 %), 5 (-22.3 %), 6  (-29.2 %).